ANALISIS MINAT DAN BAKAT PADA SISWA REMAJA MENGGUNAKAN METODE COLLABORATIVE FILTERING BERBASIS WEB - Martin Talo; Subri; Teguh Riyanto; Ruslan Djutalov (Journal of Research and Publication Innovation, 2025)
In the educational context, interests and talents are two important aspects that influence the development of adolescent students. Interest can be defined as a person's interest or inclination towards a particular field, while talent is the natural potential that an individual has to excel in that field. Each individual has their own strengths and weaknesses, their own talents and interests, all of these things are carried out and implemented according to individual character and are assisted by internal motivation and support from the environment. The aim of this research is to discuss a person's talents and interests through test results using the web to analyze individual potential to make it easier for students to make major decisions in accordance with their talents using the PHP, CSS, HTML and Database programming languages. This website will help admins in collecting data and making reports and help find out students' interests and talents.